Evaluation of Conception Rate in Nordic Dairy Cattle - Tyrisevä, Anna-Maria; Muuttoranta, Kirsi; Pösö, J.; Nielsen, U. S.; Eriksson, J.-Å.; Aamand, G. P.; Mäntysaari, Esa A.; Lidauer, Martin H. (My University, 2017)
Nordic Cattle Genetic Evaluation (NAV) has recently updated the joint Nordic fertility evaluation launched in 2005. Countries belonging to EuroGenomics Cooperative are harmonizing fertility evaluations to increase the benefit of using the common reference population for genomic evaluation. As a part of this project, NAV included also conception rate (CR) in the group of traits under evaluation. Three breeds that are included (Holstein, Nordic Red Dairy Cattle, Jersey) are evaluated separately. Data include all cows with insemination information. Each service of a cow is defined as an observation and at maximum 10 services per parity are included. Approximately 5% of the CR observations were obtained after third (heifers) or fourth service (cows). According to other biological traits in the Nordic fertility evaluation model, heifers and cows with up to three parities are treated as separate, but genetically correlated traits. For each breed, a multi-lactation repeatability animal model is fitted. Besides conventional fixed effects such as a herd  year, an insemination year  month, and an age of heifer at first service, a service number was included to account for the change in expectation if a cow failed to conceive. Additional fixed effects included are a semen type (sexed/conventional) and a heterosis. Permanent environment and additive animal effects are modeled as random. Means of CR ranged from 0.40 (Holstein third parity cows) to 0.59 (Holstein heifers). Means of Jersey cows, 0.47 on average, were clearly higher than those of Holstein cows that had the lowest means. Countries differed in the phenotypic level of CR and in frequency distribution of services. Use of sexed semen caused approximately 11% reduction in CR for all breeds and parities and inclusion of semen type into the model improved the breeding values of younger bulls having a lot of daughters inseminated with sexed semen. This was observed in genetic trends of heifers in all breeds, and in Jersey cows.
Keywords: evaluation model; genetic trend; sexed semen; conception rate; evaluation; semen; fertility